Implementation of Problem-Based Learning-Stem Strategy on Students’ Conceptual Understanding and Critical Thinking in Fundamental of Chemical Equilibrium - Prastika, Frissa Rizkihati; Dasna, I Wayan; Santoso, Aman (Jurnal Ilmu Pendidikan, 2022)
This research aims to determine differences in students’ conceptual and critical thinking of XI High School Students that teach using Problem Based Learning-STEM strategy on learning chemical equilibrium. This research use design quasi-experimental factorial 2x2 design with convenience sampling. Instruments used in this research are students’ conceptual and critical thinking tests. The result shows that (1) there are differences students’ conceptual and critical thinking in the group that learned by Problem Based Learning-STEM with the group that learned using Problem Based Learning Strategy, (2) there are differences in students’ conceptual and critical thinking based on initial abilities in the group that learned by Problem Based Learning-STEM with the group that learned using Problem Based Learning strategy, (3) there is no interaction of Problem Based Learning-STEM strategy and Problem Based Learning based on initial abilities to students’ conceptual and critical thinking